(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The revolt of 1857 marked a turning point in the historyof India. It was the heralding of a new age. It crowned the dawn of India’sindependence from the fetters of foreign rule that had bound her. It was, infact, the first essay in India’s advent to freedom. It laid the foundation ofIndian nationalism. It acted as a great inspiration to our countrymen, who feltinspired by the example set by the rebels who had died fighting the Britishdespite the heavy odds against them.